(untitled) (Bangladesh Journal of Neuroscience, 2015)
Background: Despite conflicting results from prospective studies, substantial evidence is accumulating suggesting that high Serum Ferritin was associated with Amyotrophic Lateral Sclerosis. Objective: Our aim was to find out the association of serum ferritin with Amyotrophic Lateral Sclerosis. Methods: This was a retrospective, case-control study done in the Neurology, Department of Bangabandhu Sheikh Mujib Medical University on 76 subjects with equal number of cases and controls with their age ranging from 15 to 70 years. Results: The analysis revealed that serum ferritin were significantly high in ALS patients 158.9 ± 16.6 and p= 0.004 as compared to control 104.8 ± 7.9. The proportion of patients below 40 years of age was a bit higher. Predominance in male 73.7% and female 26.3%, predominantly workers or housewife 65% followd by day labourers 26%. A large proportion of patients in both groups were non-smoker (73.7% in case and 78.9 in control group). Conclusions: High Serum ferritin is an important risk factor for ALS. A strong positive correlation was also observed between high serum iron and ALS in our study. Bangladesh Journal of Neuroscience 2015; Vol. 31 (2): 76-82